Gamma oscillatory amplitude encodes stimulus intensity in primary somatosensory cortex - Rossiter, Holly E.; Worthen, Sian F.; Witton, Caroline; Hall, Stephen D.; Furlong, Paul L. (Frontiers in Human Neuroscience, 2013)
Gamma oscillations have previously been linked to pain perception and it has been hypothesised that they may have a potential role in encoding pain intensity. Stimulus response experiments have reported an increase in activity in the primary somatosensory cortex (SI) with increasing stimulus intensity, but the specific role of oscillatory dynamics in this change in activation remains unclear. In this study, Magnetoencephalography (MEG) was used to investigate the changes in cortical oscillations during 4 different intensities of a train of electrical stimuli to the right index finger, ranging from low sensation to strong pain. In those participants showing changes in evoked oscillatory gamma in SI during stimulation, the strength of the gamma power was found to increase with increasing stimulus intensity at both pain and sub-pain thresholds. These results suggest that evoked gamma oscillations in SI are not specific to pain but may have a role in encoding somatosensory stimulus intensity.